THE EFFECT OF CONSUMER ATTITUDE ON PURCHASING INTENTION FOR ORGANIC PRODUCTS - Sandhe, Ashutosh (International Journal of Research -GRANTHAALAYAH, 2019)
This research paper examines the effect of consumer attitude on purchasing intention towards organic or eco-friendly paints. Attitude was measured through tri-component model of attitude formation. Data was collected from 300 respondents in the city of Vadodara, Gujarat, India. Respondents were administered a structured questionnaire containing statements measuring attitude in terms of cognitive, affective and conative factors. Responses were collected in the form of a five point likert scale ranging from “strongly agree” to “strongly disagree”. Consumer attitude and purchasing intention was found to be moderately favorable. The research highlighted the fact that consumers are not aware about the availability of such a product in the market. This is an important finding from the view point of marketing research.